Pemberdayaan Perempuan Desa Sendang melalui Inovasi Batik Eco Printing untuk Meningkatkan Kemandirian Ekonomi - Zulfatun Anisah; Agus Wahyu Irawan; Nurul Novitasari; Siti Fatimah; Rinatul Khumaimah (Journal of Community Engagement in Economics, 2025)
The main issue underlying this community service program is the condition of women in Sendang Village, Senori District, Tuban Regency, where the majority are housewives and young women with relatively high unemployment rates. They require guidance that provides new skills to improve their household economy. This program focuses on utilizing local potential in the form of leaves rich in natural pigments and tannins, such as teak, kersen, guava, and eucalyptus leaves, to produce eco-printing batik products. The purpose of this community service is to provide practical skills for village women so they can develop creative businesses based on local resources while simultaneously building collective awareness of economic independence and sustainable environmental management. The method applied was a participatory approach through community organizing, including stages of identifying social conditions, analyzing local resources, conducting discussions with village leaders, providing technical training in eco-printing batik, and offering assistance in business management and marketing. This strategy was strengthened through regular evaluations and the formation of women’s groups as new social institutions. The results showed increased technical skills among participants, the establishment of women’s eco-printing batik groups, the emergence of local female leaders, and greater collective awareness of the village’s economic and ecological potential. Thus, this program successfully encouraged sustainable social transformation through the integration of practical skills, women’s empowerment, and the utilization of local wisdom.